Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,435 questions

17,804 answers

1,438 comments

339,697 users

Trig Equations Question?

0 votes

Prove (1-cos(x))/(1+cos(x)) = (csc(x)-cot(x))^2

asked Nov 13, 2013 in TRIGONOMETRY by chrisgirl Apprentice

1 Answer

0 votes

Right hand side

= (cscx-cotx)^2

     [ (a-b)^2 = a^2+b^2-2ab ]

= csc^2x-2cscxcotx+cot^2x

    [ Recall the formula cscx = 1/sinx and cotx =cosx/sinx ]

= 1/sin^2x - 2*1/sinx*cosx/sinx + cos^2x/sin^2x

    [ Take out common term1/sin^2x ]

= 1/sin^2x*(1-2cosx+cos^2x)

= 1/sin^2x*(1-cosx)^2

    [ From the trigonometric identities sin^2x =1-cos^2x ]

= (1-cosx)(1-cosx)/(1-cos^2x)

= (1-cosx)(1-cosx)/ (1-cosx)(1+cosx)

   [ Cancel the common term (1-cosx) ]

= (1-cosx)/(1+cosx)

= Left hand side

answered Nov 13, 2013 by william Mentor

Related questions

asked Oct 3, 2014 in CALCULUS by anonymous
asked Oct 3, 2014 in CALCULUS by anonymous
asked Oct 3, 2014 in CALCULUS by anonymous
asked Oct 3, 2014 in CALCULUS by anonymous
asked Oct 3, 2014 in CALCULUS by anonymous
asked Oct 2, 2014 in CALCULUS by anonymous
asked Oct 2, 2014 in CALCULUS by anonymous
asked Oct 2, 2014 in CALCULUS by anonymous
asked Oct 2, 2014 in CALCULUS by anonymous
asked Oct 2, 2014 in CALCULUS by anonymous
asked Dec 5, 2014 in TRIGONOMETRY by anonymous
...